2021
DOI: 10.3390/antibiotics10080940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic-Resistant Escherichia coli Isolated from Swine Faeces and Lagoons in Bulgaria

Abstract: Antimicrobial resistance (AMR) is a worldwide health problem affecting humans, animals, and the environment within the framework of the “One Health” concept. The aim of our study was to evaluate the prevalence of pathogenic strains of the species Escherichia coli (E. coli), their AMR profile, and biofilm-forming potential. The isolated strains from three swine faeces and free lagoons (ISO 16654:2001/Amd 1:2017) were confirmed using Phoenix M50 and 16S rDNA PCR. The antibiotic sensitivity to 34 clinically appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Further MDR strains were observed for E. coli, P. aeruginosa, A. baumannii, and K. pneumoniae, while the three other species were almost exclusively found to be XDRs (Figure 4). Several studies have reported MDR Gram-negative bacteria from environmental sources where their resistance pattern was established using disk diffusion according to either EUCAST 51,52 or Clinical and Laboratory Standards Institute (CLSI) guidelines. [53][54][55][56] The high incidence of extensively…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further MDR strains were observed for E. coli, P. aeruginosa, A. baumannii, and K. pneumoniae, while the three other species were almost exclusively found to be XDRs (Figure 4). Several studies have reported MDR Gram-negative bacteria from environmental sources where their resistance pattern was established using disk diffusion according to either EUCAST 51,52 or Clinical and Laboratory Standards Institute (CLSI) guidelines. [53][54][55][56] The high incidence of extensively…”
Section: Discussionmentioning
confidence: 99%
“…Further MDR strains were observed for E. coli , P. aeruginosa , A. baumannii , and K. pneumoniae , while the three other species were almost exclusively found to be XDRs ( Figure 4 ). Several studies have reported MDR Gram-negative bacteria from environmental sources where their resistance pattern was established using disk diffusion according to either EUCAST 51 , 52 or Clinical and Laboratory Standards Institute (CLSI) guidelines. 53–56 The high incidence of extensively drug-resistant strains in both clinical and nonclinical wastewaters may be attributed to the constant selective pressure placed on the bacteria not only by the excessive use of antibiotics but also by other antimicrobial agents that are released from hospitals and other urban runoffs, eg, industrial and agricultural effluent.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, antibiotic resistance surveillance programs often use E. coli as an indicator [7][8][9]. The prevalence of antibiotic-resistant E. coli is increasing in many animals, such as poultry [22,23], swine [24][25][26], cattle [18,27,28], and wild animals [29][30][31][32]. At present, limited data exist on antibiotic-resistant E. coli and their phylogenetic groups in wild and domestic animals in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…The first pig farm for this research was the same as that in our previous study [ 25 ] (near Kostinbrod town). Samples were taken in May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…In order to continue our work in the field of antimicrobial resistance in Bulgarian farm swine samples, we tested feces and lagoons in the same way as that in our previous work [ 25 ], but this time, we include three farms as well as wastewaters, transport vehicles and soils in addition. The results concerning the antimicrobial susceptibility, GAR and biofilm formation of E. coli are presented here.…”
Section: Introductionmentioning
confidence: 99%